2014
DOI: 10.1213/ane.0000000000000107
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Labor Analgesia Is Associated with a Decreased Risk of Postpartum Depression

Abstract: Epidural labor analgesia was associated with a decreased risk of postpartum depression. Further study with a large sample size is needed to evaluate the impact of epidural analgesia on the occurrence of postpartum depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
128
2
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(142 citation statements)
references
References 41 publications
6
128
2
6
Order By: Relevance
“…The absolute difference in rates of breastfeeding initiation and duration vary by setting and are likely influenced by a range of factors such as intervention fidelity, social factors, and others. Although our scope is narrower (in terms of eligible country setting and study design), our conclusions are consistent with a recent narrative review 226 focused on BFHI; the authors conclude that adherence to the BFHI Ten Steps has a positive influence on breastfeeding outcomes. In terms of other health care interventions, staff training alone (without other breastfeeding support components) did not lead to improved breastfeeding outcomes.…”
Section: Findings In Relation To What Is Already Knownsupporting
confidence: 87%
See 1 more Smart Citation
“…The absolute difference in rates of breastfeeding initiation and duration vary by setting and are likely influenced by a range of factors such as intervention fidelity, social factors, and others. Although our scope is narrower (in terms of eligible country setting and study design), our conclusions are consistent with a recent narrative review 226 focused on BFHI; the authors conclude that adherence to the BFHI Ten Steps has a positive influence on breastfeeding outcomes. In terms of other health care interventions, staff training alone (without other breastfeeding support components) did not lead to improved breastfeeding outcomes.…”
Section: Findings In Relation To What Is Already Knownsupporting
confidence: 87%
“…We identified no eligible studies assessing workplace breastfeeding interventions; other reviews have highlighted the lack of controlled trials of workplace interventions for promoting breastfeeding in employed women. 26,226 We looked for both trials and observational studies with a control group and still found no eligible studies. The absence of evidence on this topic precludes us from commenting on the effectiveness of workplace breastfeeding interventions.…”
Section: Findings In Relation To What Is Already Knownmentioning
confidence: 99%
“…Опубликованный в 2006 г. мета-анализ U. Halbreich и S. Karkun с включени-ем 143 исследований, посвященных частоте встречаемости ПРД по всему миру, продемон-стрировал, что распространенность депрес-сии составляет от 0 до 60 % в зависимости выбранного времени оценки в послеродовом периоде и используемых шкал [6]. В Германии 3,6 % родильниц заболевают депрессией в по-слеродовом периоде [7], в Японии депрессия после родов зарегистрирована у 17 % родиль-ниц [8], в США -у 10-20 % женщин [28], в Сингапуре -у 8 % [29], в Китае -у 24,3 % [5].…”
Section: обсуждение полученных результатовunclassified
“…Критическим проявлением ПРД могут быть суицидальные мысли [1][2][3][4]. По данным различных авторов, частота встре-чаемости ПРД составляет от 0 до 60 % [5][6][7][8]. Проведенный M.W.…”
Section: Introductionunclassified
See 1 more Smart Citation